The syntheses, characterizations, X-ray crystal structures and properties of Cu(I) complexes of a bis-bidentate schiff base ligand - Mukherjee, A.; Chakrabarty, R.; Ng, S.W.; Patra, G.K. (Elsevier, 2010)
Bis-bidentate Schiff base ligand L and its two mononuclear complexes [CuL(CH3CN)(2)]ClO4 (1)and [CuL(PPh3)(2)]ClO4 (2)have been prepared and thoroughly characterized by elemental analyses, IR, UV-Vis, NMR spectroscopy and X-ray diffraction analysis. In both the complexes the metal ion auxiliaries adopt tetrahedral coordination environment. Their reactivity, electrochemical and photophysical behavior have been studied. Complex 1 shows reversible Cu-II/I couple with potential 0.74 V versus Ag/AgCl in CH2Cl2. At room temperature L is weakly fluorescent in CH2Cl2, however in Cu(I)complexes 1 and 2 the emission in quenched. (C) 2009 Elsevier B. V. All rights reserved.